'Do No Harm'? Exploring the Scope of Economic and Social Rights in Transitional Justice. (14th September 2014) - Schmid, Evelyne; Nolan, Aoife
Abstract 1 : Increasing numbers of academics and practitioners are employing the language of economic and social rights (ESR) when conceptualizing the aims, scope and implementation mechanisms of transitional justice. Their contributions have added to an evolving debate on the boundaries of transitional justice. However, when employing rights language, the current debate on the economic and social dimensions of transitional justice frequently suffers from terminological and conceptual confusion. Problematically, it is not unusual for the claims made by transitional justice commentators with regard to ESR to be founded on apparent misconceptions about both the legal framework and the existing scholarship relating to ESR. Addressing these misconceptions in terms of four key dichotomies and suggesting the way forward, we prepare the ground for a more effective debate on the desirability and feasibility of incorporating ESR into transitional justice processes. In doing so, we assert that such a debate must be based on an accurate understanding of ESR and the obligations they impose. We conclude by demonstrating how inclusion of ESR considerations in transitional justice does not necessitate rethinking transitional justice as a whole.